KERAGAAN VARIETAS DAN GALUR HARAPAN PADI GOGO PADA DAERAH ALIRAN SUNGAI BATANG ASAI SAROLANGUN JAMBI (The Performance of Upland Paddy Varietas and Lines in Batang Asai Watershed Sarolangun Jambi) - Syafri Edi (Bioplantae, 2013)
Potential of upland paddy in dryland watersheds has not been utilized optimally to support increasing food security. Main constraints of upland paddy cultivication in watershed are drought and blast disease disorders. In order to obtain high yielding upland rice varieties which is tolerant to drought and blast pathogen, five varieties have been cultivated in Batang Asai Sarolangun Jambi watersheds at May-October 2011. These varieties are Inpago 4, Inpago 5, Inpago 6, Limboto, and Towuti, 1 (one) strain expectation (B11579E-MR-7-1-1), and 1 (one) Senimas local varieties. Experiment was arranged in Randomized Block Design (RBD) with 4 replication. Results revealed that the climatic conditions are not conducive for growth and crop production, due to low in rainfall and increased rainy days.These caused unoptimal plant growth, triggered high pests population, and increased in high percentage of empty grains. The high potential was indicated by Limboto, while Towuti showed the lowest yield. High yield of Limboto was supported by high yield component. Compared to other varieties, Limboto also shows high drought tolerance . Key words : Upland Rice, watershed, drought, line